Signos banta ng nagbabagong klima - Gutierrez, Richard; Nuñez, Marilen Go.; Gatchalian, Elmer; Severino, Howie; Pulido, Maki.; Tina, Raffy; GMA News and Public Affairs (Quezon City GMA News and Public Affairs, 2008)
This program features the most pressing environmental issue today -- the world's changing climate as a result of decades of unchecked human activity.
Bonus feature: Interview with Richard Gutierrez (2 min.).
Summary from cover.
Executive producer, Marilen Go-Nuñez ; Writer, Elmer Gatchalian ; Head researcher/Associate producer, Barnaby Lo ; Field producers, Sherilyn Bruan, Arla Fabella, Mildred Fragante, Lea Llamoso, Marla Oliva, JJ Christine Villamarin.
Narrator, Richard Gutierrez ; Field reporters, Howie Severino, Maki Pulido and Raffy Tima.
DVD.
With English subtitles.
Keywords: Climatic changes; Global warming; Climatic changes -- Health aspects -- Philippines; Climatic changes -- Environmental aspects -- Philippines; Human ecology -- Philippines; Environmental protection -- Philippines; Environmental education